Desempenho da pesquisa de anticorpos anti-Leishmania (Leishmania) amazonensis, por citometria de fluxo, no diagnóstico da leishmaniose tegumentar americana - Pissinate, Jauber Fornaciari (2006)
In this work, the performance of a cytometry-based methodology to detect anti-L.(L.) amazonensis antibodies was analyzed for the diagnosis for American tegumentar leishmaniasis (ATL). As a first step, we have standardized the methodology which allowed the discrimination between patients with ATL and healthy individuals. Then, we analyzed sera from 69 patients with parasitological diagnosis for ATL (59 from cutaneous and 10 from mucosal leishmaniasis) to evaluate the performance of the methodology in diagnosing ATL. As control, sera from 34 healthy individuals and 50 patients with visceral leishmaniasis (VL), Chagas disease (CD), malária (MAL), hanseniasis (HAN) and sporotrichosis (SPO) were also assessed. Diluted sera samples were first incubated with fixed promastigote and then, with FITC conjugated anti-human IgG diluted at 1:4,000 for flow cytometry analysis. The results were expressed as percentage of positive fluorescent parasites (PPFP) for each individual sample, establishing PPFP = 25% as the cut-off between positive and negatives results. The analysis of the test performance demonstrated sensibility of 99% and specificity of 100%, when only sera from healthy individuals were considered as control. However, a decrease on the specificity (from 100% to 70%) was observed when sera from VL, CD and MAL were evaluated. Due to this cross-reaction, the performance of the test using IgG subclasses was evaluated in the diagnosis of ATL. Concerning IgG subclasses, reactivity was found only for IgG1 and IgG3. The comparative analysis of the test performance using IgG, IgG1 and IgG3 showed sensibility of 96%, 88% and 100% and specificity of 54,5%, 63% and 65% , respectively, when sera from VL, CD and MAL were analyzed. Based on our results we can conclude that this methodology can be used as an alternative tool for the diagnosis of ATL.